Client-based evaluation of the effects of localized vibration therapy on pain and mobility scores in dogs with radiographic bilateral hip dysplasia - Turner, Kristal F.; Canapp, Sherman O.; Canapp, Debra A.; Sutton, Angela M.; Canapp, Allyson; Jimenez, Isabel A.; Gerardi, Joyce (Frontiers in Veterinary Science, 2024)
Introduction: This study evaluated the effects of localized vibration (LV) in 37 dogs with bilateral hip dysplasia (HD). HD is a common cause of lameness in dogs, and is a contributory factor to osteoarthritis, which can reduce the dog's overall quality of life.This was a multi-center, prospective survey-based study of 37 dogs with bilateral HD and no prior history of surgical management. Dogs were given LV therapy daily for 14 consecutive days using the same commercially available handheld vibration device. Canine Brief Pain Index (CBPI) data was collected prior to the initiation of therapy, then for 14 days following daily LV therapy. The dogs' medications, supplements, additional rehabilitation modalities, and activity level were unchanged during the study period. Baseline CBPI pain severity and pain interference scores were compared to scores after 7 or 14 days of LV.Results: There were significant decreases in average pain severity and average pain interference CBPI scores in response to 7 and 14 days of therapy compared to baseline. When response to therapy was defined as a decrease in both pain severity score and pain interference score, 62% (23/37) of dogs responded to therapy at 7 days of treatment and 73% (27/37) responded at 14 days of treatment. Of the individuals that responded to treatment at 7 days, 91% (21/23) continued to respond at 14 days.Daily LV resulted in a significant reduction in CBPI scores in 73% of dogs with bilateral HD in this study. Randomized and blinded studies should be performed to further assess daily LV as a treatment modality for canine HD.